2021
DOI: 10.1158/1055-9965.epi-21-0686
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated Risk Variants in ANRIL Are Associated with Tumor-Infiltrating Lymphocyte Presence in Primary Melanomas in the Population-Based GEM Study

Abstract: Disclosure of Potential Conflicts of Interest: K Busam has received minor royalties from editing a textbook with Elsevier. SB Gruber is the Co-Founder of Brogent International LLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…147,148 GWASs have reported that genetic variation at ANRIL is associated with an increased risk of melanoma. 149 In one study, Maccioni et al 150 reported select variants showing a statistically significant association with the risk of melanoma, including the rs3088440 (3′ UTR CDKN2A) and variant T-allele of the tagging rs2811710 variant. In another study, also on melanoma, upregulation of ANRIL correlated with downregulation of INK4A and INK4B indicating that ANRIL exerts a probable promelanomagenesis effect via regulation of the gene locus encoding for tumor suppressors INK4A and INK4B.…”
Section: Tert †mentioning
confidence: 99%
See 1 more Smart Citation
“…147,148 GWASs have reported that genetic variation at ANRIL is associated with an increased risk of melanoma. 149 In one study, Maccioni et al 150 reported select variants showing a statistically significant association with the risk of melanoma, including the rs3088440 (3′ UTR CDKN2A) and variant T-allele of the tagging rs2811710 variant. In another study, also on melanoma, upregulation of ANRIL correlated with downregulation of INK4A and INK4B indicating that ANRIL exerts a probable promelanomagenesis effect via regulation of the gene locus encoding for tumor suppressors INK4A and INK4B.…”
Section: Tert †mentioning
confidence: 99%
“…GWASs have reported that genetic variation at ANRIL is associated with an increased risk of melanoma 149 . In one study, Maccioni et al 150 reported select variants showing a statistically significant association with the risk of melanoma, including the rs3088440 (3′ UTR CDKN2A ) and variant T-allele of the tagging rs2811710 variant.…”
Section: Genes Located Around Chromosome 9p21mentioning
confidence: 99%